A demonstration of athermal effects of continuous microwave irradiation on the growth and antibiotic sensitivity of Pseudomonas aeruginosa PAO1. (14th November 2016) - Nakouti, Ismini; Hobbs, Glyn; Teethaisong, Yothin; Phipps, David
Abstract : Stress, caused by exposure to microwaves (2.45 GHz) at constant temperature (37 ± 0.5°C), alters the growth profile of Pseudomonas aeruginosa PAO1. In the absence of microwave treatment a simple, highly reproducible growth curve was observed over 24 h or more. Microwave treatment caused no reduction in growth during the first 6 h, but at a later stage (>12 h) the growth was markedly different to the controls. Secondary growth, typical of the presence of persisters clearly became apparent, as judged by both the dissolved oxygen and the cell density profiles. These treated cells showed distinct morphological changes, but on regrowth these cells reverted to normal. The microwave induced persisters were subject to antibiotic challenge (tobramycin) and showed increased sensitivity when compared to the unstressed planktonic cells. This is in marked contrast to antibiotic induced persisters which show increased resistance. This provides evidence for both a nonthermal effect of microwaves and a previously undescribed route to a novel form of antibiotic susceptible persister cells. © 2016 American Institute of Chemical Engineers Biotechnol. Prog., 33:37–44, 2017